A magyar gazdasági vezetés professzionalizációjának két hulláma (Szociológiai Szemle, 2024)
Professionalization has two diverse meanings. In the broader sense, professionalization denotes becoming more competent, using more efficient and elaborated social processes. In the narrower sense, it means the development of the special intellectual professions.The paper examines the extent to which professionalization can apply to Hungarian economic leaders in both senses of the word. In other words, to what extent has the Hungarian economic elite become more professional over the 20th century, and to what extent has their work become a profession? It will be examined what recruitment and education, what interest-asserting modes and what attitudes characterized each generation of economic managers. Political history, the changes of systems, the dynamics of war and peace economy massively determined the course of professionalization in Hungary. The first wave of professionalization largely coincided with the first half of the 20th century, the second wave with its second half. In both waves, two generations, of leaders can be differentiated: the founders and heirs in the first, and the generations of worker managers and cadre-managers in the second.It concludes that in the narrower sense, a lame professionalization, or specialization can be found. Meritocratic and credential values were involved in the recruitment of leaders in both periods, but they were combined with opposite criteria of origin and loyalty.